HEALTH SERVICES AND EMPOWERMENT OF THE ELDERLY BASED ON LEGAL ASSURANCE PERSPECTIVE IN BOJONGLOA KALER, BANDUNG CITY - Hariningsih, Wintari (Universitas Airlangga, 2023)
Introduction: The Elderly people's prosperity as mentioned in Indonesia's Law No. 13 1998 article 1 verse (2) is those who are 60 years old or more. In this level, it happens the decrease process of relations among people, income and basic needs. Therefore, they require support from various parties in order to remain capable and adaptable so that they can live properly. To do that, integrated service posts (Posyandu) managed by community and governments indeed have an important role in improving elderly people's health. Methods: This research aims especially to explore problems of giving services of health for the elderly in Posyandu and apply some efforts to solve the problem. Qualitative descriptive research design is the type of this research to explore more about sociological law which legal materials used are primary, secondary and tertiary legislation. Results: of this study shows giving health services to elderly people held at Posyandu such as only measurements of weight, height and abdominal circumference due to the limited competence of cadres and health workers. Meanwhile those elderly have not got empowerment in their Posyandu service activities. Conclusions: it is recommended to take cross-sectoral collaboration for health care and empowerment of the elderly in the context of legal certainty, as well as, Ners as the ones who are in charge of the elderly program at the community health center.